Advancing the CGIAR-France partnership in resilient agri-food systems - International Livestock Research Institute; Centre de coopération internationale en recherche agronomique pour le développement (International Livestock Research Institute, 2025)
The ‘Advancing CGIAR – France Partnership in CGIAR Action Area: Resilient Agri-Food Systems’ workshop, on 5-6 December 2024, at CIRAD in Paris, focused on strengthening collaboration between CGIAR and French institutions in building resilient agri-food and agri-health systems. This partnership, which started in 2012, is tackling challenges in food security, nutrition, and climate change through joint research. The workshop discussed agri-health systems, identified knowledge gaps, and developed concrete actions for future collaboration, including a White Paper. One Health, sustainable food systems, and funding opportunities were also discussed.